2016
DOI: 10.1111/iere.12152
|View full text |Cite
|
Sign up to set email alerts
|

Fair Retirement Under Risky Lifetime*

Abstract: A premature death unexpectedly brings a life and a career to their end, leading to substantial welfare losses. We study the retirement decision in an economy with risky lifetime, and compare the laissez-faire with egalitarian social optima. We consider two social objectives: (1) the maximin on expected lifetime welfare (ex ante), allowing for a compensation for unequal life expectancies; (2) the maximin on realized lifetime welfare (ex post ), allowing for a compensation for unequal lifetimes. The latter optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…But that argument is not convincing: even if no one knows ex ante who will be short-lived and who will be long-lived, it is possible, by reorganizing the life cycle (in terms of consumption profiles and working periods), to minimize the well-being losses for the unlucky short-lived. As shown in Fleurbaey et al (2014Fleurbaey et al ( , 2016, this task can be done by giving up the utilitarian criterion, and by adopting a social criterion that does more justice to the idea of compensating the short-lived.…”
Section: The Ex Post Egalitarian Optimummentioning
confidence: 99%
See 3 more Smart Citations
“…But that argument is not convincing: even if no one knows ex ante who will be short-lived and who will be long-lived, it is possible, by reorganizing the life cycle (in terms of consumption profiles and working periods), to minimize the well-being losses for the unlucky short-lived. As shown in Fleurbaey et al (2014Fleurbaey et al ( , 2016, this task can be done by giving up the utilitarian criterion, and by adopting a social criterion that does more justice to the idea of compensating the short-lived.…”
Section: The Ex Post Egalitarian Optimummentioning
confidence: 99%
“…In a recent paper, Fleurbaey, Leroux, Pestieau, and Ponthiere (2016) examined how varying the age at retirement could achieve such a compensation. Fleurbaey et al (2016) characterized the optimal retirement age while adopting an ex post egalitarian social welfare criterion, which gives absolute priority to the worst-off in realized terms (who is, in general, the short-lived). Fleurbaey et al (2016) showed that the compensation of the unlucky short-lived pushes toward postponing retirement in comparison with the utilitarian social optimum.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, in the utilitarian case, health inequalities still prevail and we can be concerned that the utility of the fertile is larger than the utility of the ex-ante infertile. Because heterogeneity is not the result of any actions held by agents but rather due to circumstances (let us refer for instance to pollution exposure), we also explore alternative criteria of social evaluation according to Fleurbaey (2008), Ponthière (2016), or Fleurbaey, Leroux, Pestieau, Ponthière, andZuber (2018). More precisely, we consider an inequality averse social planner who either maximizes the expected long-run well-being of the worst-off (ex-ante egalitarian social criteria) or maximizes the long-run realized well-being of the worst-off (ex-post egalitarian social criteria).…”
Section: Introductionmentioning
confidence: 99%